AuB8−: an Au–borozene complex. Issue 19 (16th February 2022) - Chen, Wei-Jia; Zhang, Yang-Yang; Li, Wan-Lu; Choi, Hyun Wook; Li, Jun; Wang, Lai-Sheng
Abstract : Photoelectron spectroscopy and quantum chemistry studies are used to investigate the structure and bonding of AuB8 − . Abstract : Photoelectron spectroscopy and quantum chemistry studies are used to investigate the structure and bonding of AuB8 − . Global minimum sturctural searches show that AuB8 − possesses a chair-like structure, which can be viewed as Au + bonded to the edge of the doubly-aromatic B8 2− borozene, Au + [η 2 -B8 2− ]. Chemical bonding analyses reveal that the AuB8 − is a novel borozene complex with unique Au–borozene bonding.